Efisiensi Beberapa Substrat dalam Pengujian Viabilitas Benih Berukuran Besar dan Kecil (Efficiency of Several Substrates for Seed Viability Testing of Large and Small Seeds) - Faiza Chairani Suwarno; Deni Budhi Santana (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
The quality of paper substrate for seed viability testing is determined mainly by the variety and amount of the papers. A study was conducted to find  alternative paper and the optimum amount of paper for testing the viability of large and small seed with the rolled paper method. Two experiments were carried out at the Seed Science and Technology Laboratory, Bogor Agricultural University during April-September 2004 and July-December 2007. First experiment: large and small seeds represented by 5 plants (angled loofah, pumpkin, garden pea, bitter gourd, yam bean) and 7 plants (sorghum, cucumber, mungbean, soybean, horenzo, radish and wheat), respectively, were tested on 4 different paper substrates (straw, stencil, CD, and HVS) following the rolled paper method. Second experiment: large seeds of maize and ground nut, and small seeds of rice and mungbean were tested on paper substrates selected from the first experiment, straw, stencil, and CD, with different number of sheet, i.e. 2, 3, 4, and 5 sheets. Each plant seed was considered as an experiment and a randomized block design was applied to all experiments. The result indicated that for the large seeds, stencil and CD papers had equal and high similarity with the reference straw paper substrate, 100% and 80% for germination percentage and dry weight of normal seedlings, respectively. For the small seeds, only stencil paper showed high similarity for germination percentage variable, 86%, with the reference paper, whereas the other paper showed lower similarity, 57%  for both CD and HVS papers.  The second experiment showed that 2 sheets of straw, stencil or CD papers were enough for testing viability of large and small seeds to obtain germination percentage, but ground nut needs 4 sheets of straw paper. For vigor index variable, efficiency  of substrate paper on large and small seeds varied from 2 to 4 sheets. Key words:  substrate efficiency, rolled paper method, straw paper, seed size, viability testing